2001
DOI: 10.1094/phyto.2001.91.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Soil pH and the Activity of a Pelletized Nematophagous Fungus

Abstract: When formulated as assimilative hyphae in alginate pellets, the nematophagous fungus Hirsutella rhossiliensis was more active (i.e., parasitized more assay nematodes) in an acidic vineyard soil than in a neutral vineyard soil. To determine whether soil pH explained the difference, fungus activity was measured in soil from the neutral site that had been acidified (by adding sulfuric acid) and in soil from the acidic site that had been neutralized (by adding calcium hydroxide). As hypothesized, the activity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The fact that EPF have been isolated from a wide range of soils and habitats suggest that pH is not an impediment. Jaffee and Zasoski (2001) found that the nematophagous fungus Hirsutella rhossiliensis was more active (i.e., parasitized more assay nematodes) in an acidic vineyard soil than in a neutral vineyard soil. Heating the neutral soil to 608C for 2 h did not alter soil pH or electrical conductivity but increased fungus activity to levels equivalent to those in acidified soil, suggesting that the soil biota may have been influencing the efficacy of H. rhosiliensis in the neutral soil.…”
Section: Soil Phmentioning
confidence: 95%
“…The fact that EPF have been isolated from a wide range of soils and habitats suggest that pH is not an impediment. Jaffee and Zasoski (2001) found that the nematophagous fungus Hirsutella rhossiliensis was more active (i.e., parasitized more assay nematodes) in an acidic vineyard soil than in a neutral vineyard soil. Heating the neutral soil to 608C for 2 h did not alter soil pH or electrical conductivity but increased fungus activity to levels equivalent to those in acidified soil, suggesting that the soil biota may have been influencing the efficacy of H. rhosiliensis in the neutral soil.…”
Section: Soil Phmentioning
confidence: 95%
“…However, the ability of yeast (C:N 4:1) to enhance egg infection could not purely be attributed to pH, but also to the presence of additional nutrient components, including C and N, when compared to sterile distilled water. The egg infection at pH 4.5, which was the highest recorded among the pH levels tested excluding that of yeast extract, can be compared to the results reported by Jaffee and Zasoski (2001) who achieved an optimal parasitic activity of Hirsutella rhossiliensis to nematodes at pH 4.5. However, in a recent molecular study (Ward et al, 2012) reported that VCP1 (an enzyme responsible for egg infection) production was higher in more alkaline pH conditions.…”
Section: Discussionmentioning
confidence: 78%
“…Variation in soil pH from acidic to alkaline decreased the infection of RKN eggs by P. chlamydosporia (Jaffee and Zasoski, 2001), the optimum pH for growth of P. chlamydosporia being pH 5 . Little is known about the other factors affecting the parasitic activity of the fungus, including nutrition, particularly in soils rich in organic substrates.…”
Section: Introductionmentioning
confidence: 96%
“…The sandy soil used in the previous study (Chen & Liu, 2005) might favour fungal establishment as compared with clay soil in the present study. Although effects of soil texture, pH, and microbial communities on activities of H. rhossiliensis have been reported (Tedford et al, 1992;Jaffee, 1999;Jaffee & Zasoski, 2001), further studies are still needed to determine the soil factors affecting biological control effectiveness of these fungi.…”
Section: Discussionmentioning
confidence: 99%